Notes on Malagasy Discheramocephalus Johnson (Coleoptera: Ptiliidae) - Jałoszyński, Paweł (Zootaxa, 2020)
Two species of the featherwing beetle genus Discheramocephalus Johnson are known to occur in Madagascar. One of them is known from females only, and some important morphological structures have never been described and illustrated, including details of male genitalia. Morphology of the male of D. bisulcatus Darby is illustrated and described for the first time, including the aedeagus and abdominal structures, and the male genitalia of D. vasilii Darby are also illustrated in detail for the first time. Diagnoses of both species are emended to include newly described structures.